Review and Evaluation of European National Clinical Practice Guidelines for the Treatment and Management of Active Charcot Neuro-Osteoarthropathy in Diabetes Using the AGREE-II Tool Identifies an Absence of Evidence-Based Recommendations - Nichola Renwick; Jennifer Pallin; Rasmus Bo Jansen; Catherine Gooday; Aroa Tardáguila-Garcia; Irene Sanz-Corbalán; Anastasios Tentolouris; Alexandra Jirkovská; Armin Koller; Anna Korzon-Burakowska; Nina Petrova; Frances Game (Journal of Diabetes Research)
Conclusions: European national CPGs for diabetes provide limited recommendations on active CNO. All guidelines showcased deficits in their methodology, suggesting that more rigorous methods should be employed for diabetes CPG development across Europe.